2011
DOI: 10.1016/j.ajhg.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Kufs Disease, the Major Adult Form of Neuronal Ceroid Lipofuscinosis, Caused by Mutations in CLN6

Abstract: The molecular basis of Kufs disease is unknown, whereas a series of genes accounting for most of the childhood-onset forms of neuronal ceroid lipofuscinosis (NCL) have been identified. Diagnosis of Kufs disease is difficult because the characteristic lipopigment is largely confined to neurons and can require a brain biopsy or autopsy for final diagnosis. We mapped four families with Kufs disease for whom there was good evidence of autosomal-recessive inheritance and found two peaks on chromosome 15. Three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 43 publications
(87 reference statements)
1
101
0
3
Order By: Relevance
“…NCLs are a group of inherited neurodegenerative disorders characterized by lysosomal lipopigment storage mainly in neurons, and the retina is usually involved (except in the adult form of NCL, Kufs disease) 3 ; however, lysosomal lipopigment has also been reported among extracerebral tissues, including lymphocytes, skin, rectum, and skeletal muscle. Cytoplasmic vacuoles of lymphocytes may also be revealed in a blood smear examination using light microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NCLs are a group of inherited neurodegenerative disorders characterized by lysosomal lipopigment storage mainly in neurons, and the retina is usually involved (except in the adult form of NCL, Kufs disease) 3 ; however, lysosomal lipopigment has also been reported among extracerebral tissues, including lymphocytes, skin, rectum, and skeletal muscle. Cytoplasmic vacuoles of lymphocytes may also be revealed in a blood smear examination using light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Disease onset is usually in the third decade of life but onset in teenagers has also been reported. 3,4 Two gene mutations have been reported to account for the majority of patients: DNAJC5 mutations lead to the autosomal dominant inherited type Kufs disease and CLN6 mutations cause the autosomal recessive inherited type Kufs disease. 6 Cerebral MRI usually shows brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative gene loci CLN4A and CLN4B were only recently mapped. The autosomal recessive Kufs disease, CLN4A, has been shown to be caused by mutations in the CLN6 gene [25], while the autosomal dominant Kufs disease, CLN4B, has been shown to be caused by mutations in DNAJC5 that encodes cysteine-string protein alpha (CSP␣) [26]. Other NCLs that may rarely present with adult onset disease include CLN1, CLN10, CLN5, CLN13, and CLN11.…”
Section: Rakheja and Mj Bennett / Neuronal Ceroid-lipofuscinosesmentioning
confidence: 99%
“…Another group of researchers has shown a correlation between the CLN3P expression and the synthesis of bis (monoacylglycerol) phosphate (BMP) and suggested that CLN3P may play a role in the biosynthesis of BMP [24]. CLN4A (Kufs disease, autosomal recessive) has been shown to be caused by mutations in the CLN6 gene [25]. CLN4B (Kufs disease, autosomal dominant) has been shown to be caused by mutations in DNAJC5 that encodes cysteine-string protein alpha (CSP␣) [26].…”
Section: Rakheja and Mj Bennett / Neuronal Ceroid-lipofuscinosesmentioning
confidence: 99%